Sustainable Management Strategies to Enhance Business Competitiveness in the Technology Sector - Abudaqa, Anas; Geraldina, Ira; Rakhmansyah, Mohamad; Miftah, Mohammad; Dlamini, Sipho (APTISI Transactions on Management (ATM), 2024)
The increasing global demand for sustainable business practices has placed significant pressure on organizations, particularly within the technology sector, to adopt strategies that balance environmental, social, and economic goals. This study investigates the role of sustainable management strategies in enhancing business competitiveness in the technology industry. The research employs a mixed-method approach, integrating quantitative data from key performance indicators (KPIs) such as market share, operational efficiency, and innovation outcomes, with qualitative insights gathered from in-depth interviews with senior executives. The results demonstrate that companies adopting sustainability practices experience a measurable improvement in operational efficiency (10%) and market share (15%), confirming that sustainability serves as a critical enabler of competitive advantage. Qualitative findings further reveal that sustainability initiatives bolster brand differentiation, customer loyalty, and regulatory compliance, contributing to long-term success. These strategies not only help firms navigate evolving regulatory landscapes but also enhance their positioning as leaders in innovation and social responsibility. This study concludes that sustainable management strategies are essential not just for compliance, but for fostering long-term business resilience and market leadership in the fast-paced technology sector.